A method for preparing high-strength ceramic plate

By using components such as potassium feldspar and sodium feldspar in ceramic plates and materials such as fullerene trifluoromethyl derivatives, high-strength ceramic plates are prepared, which solves the problem of ceramic plates being easy to expand and contract in the environment of thermal expansion and contraction. The problem of cracking has achieved significant improvement in fracture modulus and enhanced mechanical strength.

CN118771871BActive Publication Date: 2024-12-17GUANGDONG XINRUNCHENG CERAMICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411264686.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-17
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Existing ceramic plates are prone to cracks in thermal expansion and contraction environments, have poor mechanical strength, and the fracture modulus is difficult to exceed 100MPa, which limits its application.

Method used

Dispersions are prepared by mixing potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, alumina, zirconia, hexagonal boron nitride, carbon fiber, polyoxyethylene ether and fullerene trifluoromethyl derivatives. The uniform slurry is used to form a high-strength ceramic plate by spray granulation, press molding and sintering.

Benefits of technology

The breaking modulus of the ceramic plate is significantly improved, not less than 100MPa, the mechanical strength is enhanced, the fracture is avoided, and the density and strength of the material are further improved through specific cooling rates and component ratios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of ceramic technology, and discloses a preparation method of a high-strength ceramic plate. The preparation method comprises the following steps: by weight, 30 parts of potassium feldspar, 10-20 parts of sodium feldspar, 1-5 parts of kaolin, 1-5 parts of mica powder, 10-20 parts of dolomite, 10-30 parts of aluminum oxide, 3-10 parts of zirconium oxide, 0.1-0.6 parts of hexagonal boron nitride, 0.1-0.5 parts of carbon fiber, 0.5-2 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivatives, and 10-40 parts of solvents are mixed to obtain a slurry, and then spray granulation is performed to obtain a blank, and then compression molding is performed to obtain a green blank, sintering, and a high-strength ceramic plate is obtained; the modulus of rupture of the high-strength ceramic plate is not less than 100MPa. The high-strength ceramic plate of the present invention has high mechanical strength, which is conducive to the application of high-strength ceramic plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a method for preparing a high-strength ceramic plate. Background Art

[0002] Ceramic plates are widely used. However, due to their large area and thin thickness, they are prone to cracking and other mechanical strength problems during use. The ceramic plates in the prior art contain a high quartz content, resulting in a large difference in the expansion coefficients of quartz and other components, which easily causes cracks in the use environment of thermal expansion and contraction.

[0003] The rupture modulus of the ceramic plates in the prior art is generally difficult to exceed 100 MPa, which limits the use of the ceramic plates to a certain extent.

[0004] Therefore, there is an urgent need to provide a new high-strength ceramic plate, which is conducive to the application of the ceramic plate. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing a high-strength ceramic plate. The high-strength ceramic plate of the present invention has a rupture modulus of not less than 100 MPa and high mechanical strength, which is conducive to the application of the high-strength ceramic plate.

[0006] The inventive concept of the present invention is as follows: the high-strength ceramic plate of the present invention is obtained by mixing potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, aluminum oxide, zirconium oxide, hexagonal boron nitride, carbon fiber, polyoxyethylene ether, fullerene trifluoromethyl derivative, and solvent to obtain a uniformly dispersed slurry, and then spray granulation, press molding and sintering are performed to obtain the high-strength ceramic plate. Among them, by using polyoxyethylene ether and solvent, each component (potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, aluminum oxide, zirconium oxide, hexagonal boron nitride, carbon fiber, fullerene trifluoromethyl derivative) is evenly dispersed, which is helpful to obtain a high-strength ceramic plate with uniform performance. The combination of hexagonal boron nitride, carbon fiber and fullerene trifluoromethyl derivative with other components significantly increases the strength of the sintered high-strength ceramic plate and makes it difficult to break. The special electronic structure of fullerene trifluoromethyl derivatives enables fullerene trifluoromethyl derivatives to be evenly dispersed in the slurry with carbon fibers and other components, and in the cooling process after sintering, it helps to fully release the internal stress of the material and significantly improves the density of the material, thereby significantly improving the fracture modulus of the high-strength ceramic plate. Hexagonal boron nitride has a two-dimensional structural characteristic, carbon fibers have a one-dimensional structure, and fullerene trifluoromethyl derivatives have a zero-dimensional structural characteristic. Through the interaction of these three types of structural materials, a stable spatial network structure can be formed, so that the high-strength ceramic plate has high strength.

[0007] The specific content of each component helps dispersion during the mixing process, as well as stress release and strength enhancement during sintering and cooling.

[0008] The present invention provides a method for preparing a high-strength ceramic plate, comprising the following steps:

[0009] By weight ratio, 30 parts of potassium feldspar, 10-20 parts of sodium feldspar, 1-5 parts of kaolin, 1-5 parts of mica powder, 10-20 parts of dolomite, 10-30 parts of aluminum oxide, 3-10 parts of zirconium oxide, 0.1-0.6 parts of hexagonal boron nitride, 0.1-0.5 parts of carbon fiber, 0.5-2 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivative, and 10-40 parts of solvent are mixed to obtain a slurry, and then spray granulation is performed to obtain a blank, and then compression molding is performed to obtain a green blank, and sintering is performed to obtain the high-strength ceramic plate;

[0010] The rupture modulus of the high-strength ceramic plate is not less than 100 MPa.

[0011] Preferably, the solvent includes water and a fluorine-containing solvent. The use of water and a fluorine-containing solvent together helps to better disperse the fullerene trifluoromethyl derivative and other components.

[0012] Preferably, the fluorine-containing solvent is selected from at least one of tetrafluoropropanol and hexafluoroisopropanol.

[0013] Preferably, in the solvent, the volume ratio of water to the fluorine-containing solvent is 10:(0.1-3), more preferably 10:(0.5-1).

[0014] Preferably, the fullerene trifluoromethyl derivative is selected from C 60 (CF3) 12 , C 60 (CF3) 14 , C 60 (CF3) 16 , C 60 (CF3) 18 , C 70 At least one of (CF3)6.

[0015] Preferably, spodumene is added before adding the carbon fiber.

[0016] Preferably, the amount of spodumene added is 0.1-3 parts. Adding a small amount of spodumene can adjust the crystal phase ratio of the high-strength ceramic plate and promote the strength improvement of the high-strength ceramic plate.

[0017] Preferably, the sintering temperature is 1100-1200° C., and the sintering time is 30-60 minutes; further preferably, the sintering temperature is 1150-1180° C., and the sintering time is 30-60 minutes.

[0018] Preferably, the sintering is carried out by heating the temperature to 1100-1200° C. at a rate of 5-20° C. / min.

[0019] Preferably, before the sintering, the process further includes applying a glaze, a decorative pattern and a protective glaze on the surface of the green body.

[0020] Preferably, the sintering further includes a cooling process.

[0021] Preferably, during the cooling process, the temperature is first cooled to 500-600°C at a rate of 10-15°C / min, then cooled to 200-300°C at a rate of 5-8°C / min, and finally cooled to room temperature at a rate of 3-5°C / min. At this specific staged cooling rate, the internal stress of the high-strength ceramic plate is further released, which helps to improve the fracture strength of the high-strength ceramic plate.

[0022] Preferably, a method for preparing a high-strength ceramic plate comprises the following steps:

[0023] By weight ratio, 30 parts of potassium feldspar, 14-20 parts of sodium feldspar, 2-5 parts of kaolin, 2-5 parts of mica powder, 10-20 parts of dolomite, 10-25 parts of aluminum oxide, 3-8 parts of zirconium oxide, 0.1-0.5 parts of hexagonal boron nitride, 0.1-0.3 parts of carbon fiber, 0.5-1.5 parts of polyoxyethylene ether, 0.2-0.5 parts of fullerene trifluoromethyl derivative, and 15-35 parts of solvent are mixed to obtain a slurry, and then spray granulation is performed to obtain a blank, and then compression molding is performed to obtain a green blank, and sintering is performed to obtain the high-strength ceramic plate;

[0024] The rupture modulus of the high-strength ceramic plate is not less than 100 MPa.

[0025] Preferably, the rupture modulus of the high-strength ceramic plate is 105-125 MPa, for example, 105 MPa, 110 MPa, 115 MPa, 120 MPa.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] (1) The high-strength ceramic plate of the present invention is obtained by mixing potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, aluminum oxide, zirconium oxide, hexagonal boron nitride, carbon fiber, polyoxyethylene ether, fullerene trifluoromethyl derivative, and solvent to obtain a uniformly dispersed slurry, and then spray granulation, press molding and sintering are performed to obtain the high-strength ceramic plate. Among them, by using polyoxyethylene ether and solvent, each component (potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, aluminum oxide, zirconium oxide, hexagonal boron nitride, carbon fiber, fullerene trifluoromethyl derivative) is evenly dispersed, which helps to obtain a high-strength ceramic plate with uniform performance. The combination of hexagonal boron nitride, carbon fiber and fullerene trifluoromethyl derivative with other components significantly increases the strength of the sintered high-strength ceramic plate and makes it difficult to break. The special electronic structure of fullerene trifluoromethyl derivatives enables fullerene trifluoromethyl derivatives to be evenly dispersed in the slurry with carbon fibers and other components, and in the cooling process after sintering, it helps to fully release the internal stress of the material and significantly improves the density of the material, thereby significantly improving the modulus of rupture of the high-strength ceramic plate. Hexagonal boron nitride has a two-dimensional structural characteristic, carbon fibers have a one-dimensional structure, and fullerene trifluoromethyl derivatives have a zero-dimensional structural characteristic. Through the interaction of these three types of structural materials, a stable spatial network structure can be formed, so that the high-strength ceramic plate has high strength. The modulus of rupture of the high-strength ceramic plate of the present invention is not less than 100MPa.

[0028] (2) Under the specific staged cooling rate of the present invention, it is helpful to further release the internal stress of the high-strength ceramic plate, which helps to improve the fracture strength of the high-strength ceramic plate.

[0029] (3) Adding a small amount of spodumene can adjust the crystal phase ratio of the high-strength ceramic plate, which promotes the improvement of the strength of the high-strength ceramic plate. DETAILED DESCRIPTION

[0030] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0031] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0032] The following potassium feldspar, sodium feldspar, kaolin, mica powder, dolomite, alumina, zirconium oxide, hexagonal boron nitride, spodumene material particles can pass through a 180-200 mesh sieve.

[0033] Example 1: Preparation of high-strength ceramic plates

[0034] A method for preparing a high-strength ceramic plate comprises the following steps:

[0035] By weight, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.1 parts of carbon fiber, 0.9 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 30 parts of solvent (29.5 parts of water, 0.5 parts of tetrafluoropropanol) are stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0036] Example 2: Preparation of high-strength ceramic plates

[0037] A method for preparing a high-strength ceramic plate comprises the following steps:

[0038] By weight, 30 parts of potassium feldspar, 17 parts of sodium feldspar, 3 parts of kaolin, 4 parts of mica powder, 12 parts of dolomite, 20 parts of aluminum oxide, 5 parts of zirconium oxide, 0.1 parts of hexagonal boron nitride, 0.1 parts of carbon fiber, 1.1 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 70 The mixture was stirred at 600 rpm for 40 minutes to obtain a slurry, which was then spray granulated to obtain a blank, which was then pressed to obtain a green body, and the temperature was raised to 1130°C at a rate of 12°C / min and sintered for 55 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0039] Example 3: Preparation of high-strength ceramic plates

[0040] A method for preparing a high-strength ceramic plate comprises the following steps:

[0041] By weight, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.5 parts of spodumene, 0.1 parts of carbon fiber, 0.9 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 30 parts of solvent (29.5 parts of water, 0.5 parts of tetrafluoropropanol) are stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0042] Example 4: Preparation of high-strength ceramic plates

[0043] A method for preparing a high-strength ceramic plate comprises the following steps:

[0044] By weight, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.1 parts of carbon fiber, 0.9 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 30 parts of solvent (29.5 parts of water, 0.5 parts of tetrafluoropropanol) at 500 rpm, stir and mix for 50 minutes to obtain a slurry, then spray granulate to obtain a blank, then press mold to obtain a green body, heat to 1150°C at a rate of 10°C / min, sinter for 50 minutes, then first cool to 500°C at a rate of 10°C / min, then cool to 300°C at a rate of 6°C / min, and finally cool to room temperature at a rate of 3°C / min to obtain a high-strength ceramic plate.

[0045] Comparative Example 1

[0046] Compared with Example 1, the difference of Comparative Example 1 is that an equal amount of C 60 Instead of the fullerene trifluoromethyl derivative (C 60 (CF3) 12 ), the specific contents of Comparative Example 1 are as follows:

[0047] A method for preparing a ceramic plate comprises the following steps:

[0048] According to the weight ratio, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.1 parts of carbon fiber, 0.9 parts of polyoxyethylene ether, C 60 0.3 parts of tantalum and 30 parts of solvent (29.5 parts of water and 0.5 parts of tetrafluoropropanol) were stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which was then spray granulated to obtain a blank, which was then pressed to obtain a green body, and the temperature was raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a ceramic plate.

[0049] Comparative Example 2

[0050] Compared with Example 1, the difference of Comparative Example 2 is that an equal amount of cubic boron nitride is used to replace the hexagonal boron nitride in Example 1. The specific content of Comparative Example 2 is as follows:

[0051] A method for preparing a high-strength ceramic plate comprises the following steps:

[0052] By weight, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of cubic boron nitride, 0.1 parts of carbon fiber, 0.9 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 30 parts of solvent (29.5 parts of water, 0.5 parts of tetrafluoropropanol) are stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0053] Comparative Example 3

[0054] Compared with Example 1, the difference of Comparative Example 3 is that an equal amount of graphene oxide is used to replace the carbon fiber in Example 1. The specific content of Comparative Example 3 is as follows:

[0055] A method for preparing a high-strength ceramic plate comprises the following steps:

[0056] By weight, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 4 parts of kaolin, 3 parts of mica powder, 12 parts of dolomite, 15 parts of aluminum oxide, 4 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.1 parts of graphene oxide, 0.9 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 30 parts of solvent (29.5 parts of water, 0.5 parts of tetrafluoropropanol) are stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0057] Comparative Example 4

[0058] Compared with Example 1, the difference of Comparative Example 4 is that an equal amount of polyethylene glycol is used to replace the polyoxyethylene ether in Example 1, and the amount of some components is changed. The specific content of Comparative Example 4 is as follows:

[0059] A method for preparing a high-strength ceramic plate comprises the following steps:

[0060] By weight, 30 parts of potassium feldspar, 8 parts of sodium feldspar, 2 parts of kaolin, 12 parts of mica powder, 12 parts of dolomite, 3 parts of aluminum oxide, 6 parts of zirconium oxide, 0.2 parts of hexagonal boron nitride, 0.1 parts of carbon fiber, 0.9 parts of polyethylene glycol, and a fullerene trifluoromethyl derivative (C 60 (CF3) 12) 0.3 parts and 30 parts of water are stirred and mixed at 500 rpm for 50 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1150°C at a rate of 10°C / min and sintered for 50 minutes, and then naturally cooled to room temperature to obtain a high-strength ceramic plate.

[0061] Product effect testing

[0062] The high-strength ceramic plates prepared in Examples 1-4 and the ceramic plates prepared in Comparative Examples 1-4 were taken, and the rupture modulus of the high-strength ceramic plates were tested according to the test method in GB / T3810.4-2016 "Determination of rupture modulus and breaking strength", and the results are shown in Table 1.

[0063] Table 1

[0064]

[0065] It can be seen from Table 1 that the high-strength ceramic plate prepared in the embodiment of the present invention has significantly better performance than the ceramic plates of Comparative Examples 1-4.

[0066] It can be seen from Example 1 and Comparative Examples 1-4 that the fullerene trifluoromethyl derivatives in the embodiments of the present invention are relatively 60 For fullerene, it can improve the dispersibility of components and increase the strength of ceramic plates; hexagonal boron nitride has a two-dimensional layered structure relative to cubic boron nitride, carbon fiber has a one-dimensional structure, and fullerene trifluoromethyl derivatives have a zero-dimensional structure. Through the interaction of these three types of structural substances, a stable spatial network structure can be formed, so that the high-strength ceramic plate has high strength. After cubic boron nitride replaces hexagonal boron nitride, it cannot form a stable spatial network structure, which is not conducive to improving the strength of the ceramic plate. Although graphene oxide is also a carbon material, it cannot replace carbon fiber to form a stable spatial network structure.

Claims

1. A method for preparing a high-strength ceramic plate, characterized in that: The following steps are involved: By weight ratio, 30 parts of potassium feldspar, 10-20 parts of sodium feldspar, 1-5 parts of kaolin, 1-5 parts of mica powder, 10-20 parts of dolomite, 10-30 parts of aluminum oxide, 3-10 parts of zirconium oxide, 0.1-0.6 parts of hexagonal boron nitride, 0.1-0.5 parts of carbon fiber, 0.5-2 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivative, and 10-40 parts of solvent are mixed to obtain a slurry, and then spray granulation is performed to obtain a blank, and then compression molding is performed to obtain a green blank, and sintering is performed to obtain the high-strength ceramic plate; The rupture modulus of the high-strength ceramic plate is not less than 100 MPa; The solvent includes water and a fluorine-containing solvent; The fluorine-containing solvent is selected from at least one of tetrafluoropropanol and hexafluoroisopropanol.

2. The preparation method according to claim 1, characterized in that: In the solvent, the volume ratio of water to the fluorine-containing solvent is 10:(0.1-3).

3. The preparation method according to claim 1, characterized in that: The fullerene trifluoromethyl derivative is selected from C 60 (CF3) 12 , C 60 (CF3) 14 , C 60 (CF3) 16 , C 60 (CF3) 18 , C 70 At least one of (CF3)6.

4. The preparation method according to claim 1, characterized in that: The sintering temperature is 1100-1200° C., and the sintering time is 30-60 minutes.

5. The preparation method according to claim 1, characterized in that: Before the sintering, the process also includes applying a glaze, a decorative pattern and a protective glaze on the surface of the green body.

6. The preparation method according to claim 1, characterized in that: The sintering process also includes a cooling process.

7. The preparation method according to claim 6, characterized in that: During the cooling process, the temperature is first cooled to 500-600° C. at a rate of 10-15° C. / min, then cooled to 200-300° C. at a rate of 5-8° C. / min, and finally cooled to room temperature at a rate of 3-5° C. / min.

8. The preparation method according to any one of claims 2 to 7, characterized in that: The rupture modulus of the high-strength ceramic plate is 105-125 MPa.

Citation Information

Patent Citations

  • Method for preparing polycrystalline cubic boron nitride synergistically-toughened by three dimensional materials

    CN107500778A

  • High-strength and high-toughness ceramic rock plate and preparation method thereof

    CN115849888A

  • Preparation method of wear-resistant composite material

    CN118027588A